ANALISIS FAKTOR PENYEBAB DISABILITAS PADA ANAK BERKEBUTUHAN KHUSUS (ABK) - Fira Sekarani; Nuralifah Zakiyyah; Tia Rahmania; Septi Fitri Meilana4 (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
This article discusses problems in children with special needs (ABK), especially in children with Attention Deficit Hyperactivity Disorder (ADHD). This article aims to identify the factors that cause children to have special needs, with the main focus on children with Attention Deficit Hyperactivity Disorder (ADHD). The method used in this study is observation and in-depth interviews with parents of children diagnosed with ADHD. The data collection method is qualitative with triangulation data collection techniques, namely interview, observation, and documentation analysis. The results of a case study show that ABK with an Attention Deficit Hyperactivity Disorder (ADHD) can be caused by genetics, environmental toxins, and psychological factors, and parents who have a history of ADHD will most likely pass it on to their children. Advice from researchers that during pregnancy, it is very important to consider the right choice of food and nutrition. Pregnant women should not consume raw seafood, because raw seafood can interfere with the development of foetal nerves.